Erosion and Deposition on Migrating Shoreface-attached Ridges, Sable Island, Eastern Canada - Dalrymple, R.; Hoogendoorn, E. (Geoscience Canada, 1997)
Summary The shoreface-attached ridges presentalong the south side of Sable Island, Nova Scotia, are the largest and deep-est yet described, but become smaller and finer grained to the east because of decreasing energy levels. Strong, along-shore, storm currents cause them to migrate eastward at rates that may reach 50 ma'. Their migrating troughs erode underlying sediments, modifying the wave-ravinement surface and creating shoreline-oblique depressions up to 12m deep. Deposition occurs on their leeside, in the form of gently dipping, graded storm beds up to 1.2 m thick containing both high-angle cross bedding and hum-mocky cross-stratification. Overall, the ridge deposits coarsen upward and re-semble shoreface successions. Obliquely onshore, cross-ridge flow causes upbuilding by the Huthnance process and accounts for the unusually high angle (~ 50°) between the ridges and the shoreface.